Pulmonary artery-targeted low-dose metformin-loaded nanocapsules safely improve pulmonary arterial hypertension in rats - Chida-Nagai, Ayako; Masaki, Naoki; Sato, Hiroki; Kato, Tatsuya; Takakuwa, Emi; Matsuno, Yoshihiro; Manabe, Atsushi; Takeda, Atsuhito (Frontiers in Pharmacology, 2025)
IntroductionPulmonary arterial hypertension (PAH) remains a challenge to tackle despite various available medications. Metformin, although promising, has major adverse effects; the use of an appropriate drug delivery method may improve its efficacy and safety. The aim of this study was to develop a novel treatment for PAH using metformin. We developed a novel approach of using low-dose metformin encapsulated in pulmonary artery-targeted nanocapsules to alleviate PAH while avoiding adverse effects.MethodsMetformin-loaded lung-targeted nanocapsules (MET nanocapsules) were created using a specific lipid composition, including cationic lipids. Their uptake and effects on cell viability were assessed in human pulmonary arterial smooth muscle cells (hPASMCs) from healthy individuals and patients with PAH. Their therapeutic effects were assessed in a PAH rat model. The safety of MET nanocapsules was confirmed using rat serum biochemical tests.ResultsWe successfully prepared MET nanocapsules and demonstrated their effectiveness in inhibiting PASMC proliferation. In PAH model rats, MET nanocapsule treatment led to improved hemodynamics, right ventricular hypertrophy, and pulmonary arterial medial thickening. The nanocapsules effectively accumulated in the lungs of PAH model rats.ConclusionIntravenous administration of MET nanocapsules is a safe and innovative therapeutic approach for PAH. This method could improve PAH treatment outcomes while minimizing adverse effects, with potential applications in other types of pulmonary hypertension.